THE EFFECT OF INTERPERSONAL COMMUNICATION, WORKLOAD AND WORK ENVIRONMENT ON WORK EFFECTIVENESS AND ORGANIZATIONAL COMMITMENTS AS INTERVENING VARIABLES IN THE REGIONAL SECRETARY OFFICE IN BINTAN DISTRICT - Hendrik Caros Nugraha; Chablullah Wibisono; Muhammar Khaddafi; Diana Titik Windayati; Fatahurrazak Fatahurrazak (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to analyze the effect of interpersonal communication, workload and work environment on work effectiveness and organizational commitment as intervening variables at the Regional Secretariat Office in Bintan Regency. The research method uses a quantitative approach with a causal design. The population of this study was all employees at the Regional Secretariat Office in Bintan Regency, with a total of 133 people. In this study, the sampling technique was non-probability sampling with the Saturated Sampling (Census) technique with a total sampling of 133 people. Data collection techniques using questionnaires and documentation. Data analysis using SEM analysis with PLS.The results of the study are as follows: (1) The effect of Interpersonal Communication on Work Effectiveness is positive and significant. (2) The effect of workload on work effectiveness is positive and not significant. (3) The influence of the work environment on work effectiveness is positive and significant. (4) The effect of Organizational Commitment on Work Effectiveness is positive and significant. (5) The effect of Interpersonal Communication on Organizational Commitment is positive and significant. (6) The effect of workload on organizational commitment is positive and significant. (7) The effect of work environment on organizational commitment is positive and significant. (8) The effect of Interpersonal Communication on Work Effectiveness variable with Organizational Commitment as an intervening variable is positive and significant. (9) The effect of Workload on Work Effectiveness variable with Organizational Commitment as an intervening variable is positive and significant. (10) The effect of Work Environment on Work Effectiveness variable with Organizational Commitment as an intervening variable is positive and not significant.